Trace metal concentration in atmospheric aerosols in some city areas of Bangladesh - Mondol, MN; Khaled, M; Chamon, AS; Ullah, SM (Bangladesh Journal of Scientific and Industrial Research, 2015)
Aerosol particulate matter and trace gases were sampled at five locations in the city areas of Bangladesh. The sampling sites were selected in the city areas near motor vehicles run with heavy traffic. The average concentrations of total suspended particulate matter in city ambient air were 413.02, 292.63, 671.65, 184.09 and 301.13 ?g m-³ in Dhaka, Noakhali, Chittagong, Faridpur and Kustia, respectively, which were higher than the daily average value, given by WHO and US EPA standard. The highest SPM concentration is in Chittagong (671.65 ?g m-³) and the lowest in Faridpur (184.09 ?g m-³). The city areas studied fall in the Unhealthy to Extremely Unhealthy class according to the Air Quality Index, 2003. Trace metal concentrations of total suspended particulate matter in city ambient air were analyzed. The reported previous Pb concentration in farmgate, Dhaka was 1238 ng m-3 by Biswas et al., (2003) and now shows a decreasing tendency, presumably due to the ban on the use of leaded fuel. The average results of trace metals have been compared to national and international standards. The Cu and Zn concentration of current study is found very high in comparison with other previously reported results. The air of Chittagong city is highly polluted. Motor vehicles, especially two stroke engine vehicles are increasingly major sources of air pollution in Chittagong. DOI: http://dx.doi.org/10.3329/bjsir.v49i4.22630 Bangladesh J. Sci. Ind. Res. 49(4), 263-270, 2014